THE IDEOLOGY CONTAINED BEHIND THE REPRESENTATION OF BALINESE WOMEN IN GEGURITAN BASUR AND THE NOVEL BASUR - Erawan, Dewa Gede Bambang; I Nyoman Suarka; I Wayan Cika; Suardiana, I Wayan (International Journal of Social Science, 2025)
Through the analysis of the ideology contained behind the representation of Balinese women in Geguritan Basur and Basur Novel, this study aims to reveal how the construction of Balinese women is formed in the text, as well as what ideology is contained behind the representation of Balinese women in Geguritan Basur and Basur novel. This study is significant because it can reveal how literary texts help maintain, challenge, or reshape views on women in Balinese society. This study uses a qualitative approach with a constructionist foundation and Michel Foucault's discourse analysis model. The aim is to analyze and find the ideology behind the representation of Balinese women in Geguritan Basur and Basur novel. The researcher is the main instrument (human instrument) whose job is to select data, analyze, interpret, and conclude. The method used in data collection is a literature study, with reading, note-taking, and interview techniques. Data analysis is carried out descriptively and qualitatively and with the following stages: reading data, marking, classifying, analyzing, and interpreting using the theories of Representation, Gender Equality, and Intertextuality. The results of this study indicate that the ideology behind the representation of Balinese women in Geguritan Basur and the Basur novel includes autonomy in determining a partner, inclusive education, free humans, and criticism of the patrilineal system